(untitled) (Journal of Academic Research, 2026)
This study aims to examine the effect of intellectual capital, with its main components—human capital, structural capital, and relational capital—on organizational innovation within the Libyan Audit Bureau’s public administration. A descriptive correlational approach was employed to determine the role of intellectual capital components in fostering organizational innovation. This was achieved by collecting quantitative data through questionnaires distributed to a sample of (269) participant. Data were then statistically analyzed using the Statistical Package for Social Sciences (SPSS). The results indicated moderate levels for both variables, with mean value of (3.31) for intellectual capital and (3.13) for organizational innovation. The mean value for the human capital dimension was (3.43), representing a higher value than the other dimensions: structural capital (3.21) and relational capital (3.28). The mean scores for innovation as an outcome and innovation as a process were (3.21) and (3.13), respectively. The results also confirmed a statistically significant impact (α ≤ 0.05) of intellectual capital on organizational innovation, with a coefficient (R² = 0.599). Linear regression analysis revealed that structural capital is the primary driver, with a coefficient (R² = 0.490), followed by relational capital (R² = 0.434), and then human capital (R² = 0.387). The study recommends developing human capital through knowledge management to bridge the gap between knowledge and application within the Bureau. It also recommends developing structural capital to enhance flexibility and decision-making speed. It suggests adopting a instrumental innovation approach, encouraging innovative initiatives, motivating efforts, and mitigating concerns associated with new innovations within the Bureau.